Implementation of the Servqual Method as a Service Support Decision Support System in Hotels (Universitas Negeri Semarang, 2019)
Hospitality is one component of the tourism industry as a means of moving in the field of services that provide services to visitors. In the current era of globalization, several companies focus on the priority of customer satisfaction. The rapid development of information technology requires companies in various fields to provide fast and appropriate solutions to address the needs or desires of the customer, included in the field of hospitality. For finding out the service quality attributes, a support decision system can be developed for service improvements in hotels. The data used in this research are data obtained from one of the four-star hotels in the city of Semarang, which are 150 data for hotel visitors and 80 for employees in the hotel, this study began in April-May 2018. Implementation of the Decision Support System (DSS) on the system produces a gap value that has the greatest value will be a concern and a priority in improving hotel services. By applying the Service Quality (Servqual) method, the first rank is Assurance with the gap value of -0.11, the second is Empathy with the gap value of -0.17, the third is Reliability with the gap value of -0.19, the fourth is Responsiveness with the gap value of -0.31, and the fifth is Tangibles with the gap value -1.39. So, it was concluded that the overall value is negative, which means it has not met customer expectations. These findings indicate that the dimensions of Tangibles need to be revisited.